Efek Magneto-Impedansi Frekuensi Rendah pada Non Litografi Multilayer [NiFe/Cu]4 - Wahyu Eko Prastyo; Budi Purnama; Nuryani Nuryani (Jurnal Fisika FLUX, 2019)
The magneto-impedance effect in multilayer system of [NiFe/Cu]4 present at this paper. The samples prepare by electrodepositin methods on a non-lithography pattern of PCB Cu substrate. The NiFe and Cu layer sequency produce to obtain a multilayer system [NiFe/Cu]4. Thereafter, sample evaluate magnetic property by using vibrating sample magnetometer (VSM).  Finally, sample evaluate a magneto-impedance response by total electrical impedance measure under various external magnetic field.  Typical magneto-impedance ratio of 7,56% indicate the sample can to apply as magnetic sensor at low frequency region.